Dawr Tajribat "Bandongan” al-Ta‘līmīyah fī al-Qudrah ‘alá Tarjamat al-Mubtada’ wa-al-Khabar min Wajhat Naẓar Ṭalabat Qism Ta‘līm al-Lughah al-‘Arabīyah - Kamila, Annisa Nabhan; Salma, Qatrunnada Habibah; Tsabit, Ubaidillah (Alsina : Journal of Arabic Studies, 2024)
The learning method for the Yellow Book in Islamic boarding schools uses the Arabic translation of Pegon to make its meaning. Pegon Arabic translation is one of the local wisdoms and traditions of studying medieval Islamic texts in the education system implemented by traditional Islamic boarding schools in Java which is still used today. This research takes the form of field research with research methods in the form of qualitative methods, namely data collection techniques by filling out questionnaires and tests. What defines Bandongan is a learning activity that has an approach that prioritizes collective service (collective approach). Mubtada linguistically means starting, so in nahwu science terms mubtada is the term at the beginning of a sentence in the form of ma'rifah. Meanwhile, Khobar is the isim read by Rofa, side by side with mubtada. So the definition of Mubtada Khobar is two isim which form the composition of the number of ismiyyah (perfect sentences). Based on the results of data collection using a questionnaire conducted on 26 students in the PBA 3B class, researchers found that almost 100% of the PBA 3B Class of 2022 students had studied the book. From the test results, it can be seen that almost 80% of students who have studied using the bandongan method have the ability to translate well based on the data presented above, so the author concludes that reciting the Koran using the bandongan method is more common than the sorogan method. In bandongan method activities, students do not need to demonstrate their ability to read or translate the yellow book. And in this activity students only pay attention, write, listen and listen to kiai when translating a book into Javanese. Bandongan has been used for a long time by some Indonesian people in Islamic boarding schools, especially in Central Java and East Java.